2017
DOI: 10.1186/s13617-017-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking computational fluid dynamics models of lava flow simulation for hazard assessment, forecasting, and risk management

Abstract: Numerical simulations of lava flow emplacement are valuable for assessing lava flow hazards, forecasting active flows, designing flow mitigation measures, interpreting past eruptions, and understanding the controls on lava flow behavior. Existing lava flow models vary in simplifying assumptions, physics, dimensionality, and the degree to which they have been validated against analytical solutions, experiments, and natural observations. In order to assess existing models and guide the development of new codes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 62 publications
0
44
0
1
Order By: Relevance
“…However, more sophisticated lava flow modelling efforts, including stochastic slope-controlled models (Harris and Rowland 2001;Favalli et al 2005), cellular automata models (Crisci et al 2004;Del Negro et al 2005;Vicari et al 2007), and other numerical simulations (Dietterich et al 2015), also rely on high quality DEMs input layers to produce successful results. UAS provide a means of effectively generating these needed DEMs, regardless of the modeling method.…”
Section: Applications For Other Lava Flow Modelsmentioning
confidence: 99%
“…However, more sophisticated lava flow modelling efforts, including stochastic slope-controlled models (Harris and Rowland 2001;Favalli et al 2005), cellular automata models (Crisci et al 2004;Del Negro et al 2005;Vicari et al 2007), and other numerical simulations (Dietterich et al 2015), also rely on high quality DEMs input layers to produce successful results. UAS provide a means of effectively generating these needed DEMs, regardless of the modeling method.…”
Section: Applications For Other Lava Flow Modelsmentioning
confidence: 99%
“…Data collected by cameras can be analyzed both manually and automatically using computer vision tools, to extract information about the evolution of each flow over the course of the experiments. Analysis can include tracking the flow front position and the flow width or thickness over time [e.g., Blake, 1990;Balm− forth et al, 2000], as these are observables that are di− rectly comparable with predictions from analytical or numerical models [Cordonnier et al, 2015;Dietterich et al, 2017]. A more complete dataset on the velocity dis− tribution of the flow surface can be obtained using techniques such as Particle Image Velocimetry (PIV) [e.g., Applegarth et al, 2010] or Optical Flow [e.g., Horn and Schunck, 1981;Lucas and Kanade, 1981;Lev et al, 2012].…”
Section: Tools and Techniquesmentioning
confidence: 99%
“…The experiments reported by Diet− terich et al [2015] were performed using sugar syrup (a Newtonian, isoviscous fluid) and molten basalt. The re− sults from the experiments have already been used as a benchmark test to numerical flow models, as sum− marized by Dietterich et al [2017]. Flow inflation be− hind an obstacle appeared to be a challenge for most codes tested, yet its importance cannot be overstated, especially in the context of flow hazard mitigation and flow diversion.…”
Section: Obstaclesmentioning
confidence: 99%
“…MOLASSES (MOdular LAva Simulation Software for Earth Science), a lava flow simulator modified from the LavaPL algorithm of Connor et al (2012), distributes lava between cells based on rules that govern flow behavior (Kubanek et al, 2015). MOLASSES has been successfully benchmarked (Dietterich et al, 2017), performs well at recreating flow geometries similar to those found on the ESRP (Fig. DR2), and is sensitive to the geometries of lava flows, their thickness, area, and the underlying topography, rather than to the mechanics of lava flow emplacement.…”
Section: Lava Flow Simulationmentioning
confidence: 99%